Crises Management for Goal Attainment in Public Secondary Schools in Bonny, Rivers State: Importance of Planning - Ohia, Adanma Ngozi (Advances in Social Sciences Research Journal, 2019)
This study examined how crises can be managed in public secondary schools in Bonny Local Government Area of Rivers State, Nigeria. Two research questions guided the study which adopted descriptive survey design. The sample was 150 staff made up of 134 teachers and 16 principals, census sampling technique was used. A researcher-structured instrument titled “Crises Management for Goal Attainment Questionnaire’’ (CMGAQ), was used to collect data. Three experts in the area of measurement and evaluation validated the instrument. The reliability was established using Pearson Product Moment Correlation which yielded a reliability index of 0.89. The research questions were answered using mean and standard deviation. Findings showed effective planning, free flow of communication and joint problem-solving as being important in crises management. Recommendations include the need for principals to plan ahead how to avert crises, use good communication skills in managing crises including ensuring the existence of good relationship between the school and the host community.